Pengaruh Literasi Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa Jurusan Pendidikan Ekonomi Universitas Negeri Gorontalo - Rika Wati Mahmud; Melizubaida Mahmud; Abdulrahim Maruwae; Radia Hafid; Imam Prawiranegara Gani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to determine whether enterpreneurial literacy influences enterpreneurial interest among the Department of Economics Education students at Universitas Negeri Gorontalo. A descriptive quantitative approach was employed, with a total sample of 148 respondents. The instrument of the study was a questionnaire, with the data analysis applied was simple linear regression.The correlation coefficient test result showwed a person correlation coefficient of 0.782, indicating a moderately strong relationship between Enterpreneural Literacy (X) and Enterpreneurial Interest (Y). the coefficient of determination test yielded an R-Square value of 0.611, indicating that Enterpreneurial Literacy addresses 61.1% of the variability in students Enterpreneurial Interest.in contrast, the remaining 38,9% is influenced by other variables not examined in this study.